2012
DOI: 10.1097/anc.0b013e3182677bc1
|View full text |Cite
|
Sign up to set email alerts
|

NICU Nurses' Lived Experience

Abstract: Nurses in this study struggled with issues of beneficence and nonmaleficence and were not aware of scientific evidence that guides methadone management of pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 6 publications
0
29
0
4
Order By: Relevance
“…Nurses in all regions across the U.S. might not be prepared for a vulnerable population who have unique challenges due to infrequent cases. Nevertheless, neonatal nurses hold a variety of ethical expectations as detailed in the American Nurses Association Code of Ethics 18 and therefore must be prepared to meet the challenges of caring for infants in drug withdrawal. Ethical principles drive the nurse’s motivation and actions when caring for the patient, especially in the context of infants in drug withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses in all regions across the U.S. might not be prepared for a vulnerable population who have unique challenges due to infrequent cases. Nevertheless, neonatal nurses hold a variety of ethical expectations as detailed in the American Nurses Association Code of Ethics 18 and therefore must be prepared to meet the challenges of caring for infants in drug withdrawal. Ethical principles drive the nurse’s motivation and actions when caring for the patient, especially in the context of infants in drug withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nurses participating in Maguire et al's study were inquired about the reason for low support. They mentioned various reasons, including the aggressive behavior of the substance-dependent mothers towards nurses [18]. To justify the inconsistency in these findings, the different geographic locations and the research site of these two studies must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The archived results also revealed no significant difference between the mean scores of nurses' support in the two groups. Similarly, Maguire et al reported that nurses required additional knowledge for providing care to substance-dependent parents [18].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of the relationships between maternity nurses and pregnant and postpartum women, these relationships may be challenged when the women use substances. Maternity nurses may experience frustration towards women with SUDs and remain emotionally distance from them, resulting in workplace stress and burnout (Fraser et al, 2007;Maguire et al, 2012;Murphy-Oikonen et al, 2010;Shaw et al, 2016).…”
Section: Relationships Between Maternity Nurses and Women With Sudsmentioning
confidence: 99%
“…As with other health care providers, however, relationships between maternity nurses and pregnant and postpartum women can be fraught with difficulties when women have used substances during pregnancy. Maternity nurses report concerns that women with SUDs are not truthful their substance use, cannot properly care for their infants, and blame nurses for their infants' problems (Fraser et al, 2007;Maguire et al, 2012;Murphy-Oikonen et al, 2010;Shaw et al, 2016). Moreover, some maternity nurses report having experienced abusive and threatening behavior from parents and family members of infants with NAS (Maguire et al, 2012).…”
Section: Relationships Between Maternity Nurses and Women With Sudsmentioning
confidence: 99%